IMPLEMENTASI PROGRAM MAKASSAR TIDAK RANTASA (Studi Pengelolaan Sampah Berbasis Partisipasi) - Kadir, Nuryadi (Jurnal Berita Sosial, 2018)
This study merupakaan review of the study of community empowerment in the context of urban phenomenon (urban) complex problems. Arrangement of cities that implicate the healthy lifestyle and clean, is an agenda in building collective awareness. Participation in waste management becomes a comprehensive performance framework for every urban, major city of Makassar. The community discourse in Makassar City related to waste management is a participatory public policy narrative. The Jargon "Makassar Towards the City of the World" needs to be manifested in a suistanable development performance. Reflections from the main jargon are fragmented in the waste policy of "Makassar Not Rantasa (MTR)". Terminology "Makassar Not Rantasa (MTR)" is considered as a locally based discourse of participation. So this research will study descriptively with some approach of study of community empowerment. Based on the result of the research, Firstly, structurally, waste management in Kota Makassar runs regulatively, achievement in cleanliness and garbage like Adipura 2015 shows good waste management. However, technically, the Makassar Program No Rantasa as a waste management is still considered to be ineffective and efficient, the garbage service program is still experiencing problems in the field, such as the provision of garbage bins, garbage fleet which still reap the problem, which is not all the amount of waste generation transported that happens is the accumulation of several points in the city of Makassar. Both participation-based waste management has not touched the public's awareness. Community empowerment and involvement is only at the technical level and the mechanism of transporting waste. Empowerment has not touched on the level of participation in initiating innovation of waste management. The policy model has not yet described the existence of public consultation in solidifying waste management, major in the zero waste program (minimizing waste volume from source). Encouraging community collective awareness through waste-related empowerment models does not yet have a suistanable framework. Therefore, there is an impasse on the level of praxis in the development of future waste management. Innovation and initiation of community-based waste management (institutional) has not been welcomed and received a positive response by the government of Makassar as a form of sustainability of waste management. because the waste management framework is still understood as a conventional and circulative conventional performance dimension Keywords: Participation, Waste Management and Empowerment